Состав и свойства золы и шлака ТЭС: справочное пособие - Пантелеев В. Г. Валерий Геннадьевич; Ларина Э. А. Эльвира Александровна; Мелентьев В. А. Владимир Александрович; Сергеева Т. Е. Таисия Ермолаевна; Мокрушин А. Р. Аркадий Романович (Ленинград, Энергоатомиздат, 1985)
Авт. указаны на обороте тит. л.